The archives of the lords of El Viso, in los Alcores, Seville - Sánchez González, Antonio (Revista General de Información y Documentación, 2021)
The locality of El Viso del Alcor separated from the district of Carmona and from the King’s jurisdiction at the end the 14th century, when it became the property of different lords. In 1440, El Viso was incorporated into the hands of the Saavedra family, a Seville-based lineage which had managed to gather large estates due to their support to the king in the wars against the Kingdom of Granada and mostly owned the city of Castellar, which was close to Gibraltar. In 1539 Carlos V granted to Juan de Saavedra the title of count of Castellar, in return to the path of service to the Crown lik lords of vassals and military leader on the border of Granada, lineage Saavedra starring came from the late Middle Ages. From the 17th century onwards, the Lords of El Viso and Counts of Castellar related to other noble houses in Spain, which made their Archive pass into the hands of the Dukes of Santisteban del Puerto during the 18th century and, later, into the hands of the Dukes of Medinaceli in 1818 definitely. This paper aims to make known the archives of the Lords of El Viso from its creation to present day. We will provide a detailed analysis of the documents contained and will also cast some light onto their organization and current arrangement in an attempt at opening a path for future works on these archives.